Study of Second Generation High Temperature Superconductors: Electromagnetic Characteristics and AC Loss Analysis - Shen, Boyang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This thesis introduces a systematic study on Second Generation (2G) High Temperature Superconductors (HTS), covering a novel design of an advanced medical imaging device using HTS, and an in-depth investigation on the losses of HTS. The text covers the design and simulation of a superconducting Lorentz Force Electrical Impedance Tomography. This is potentially a significant medical device that is more efficient and compact than an MRI, and is capable of detecting early cancer, as well as other pathologies such stroke and internal haemorrhages. It also presents the information regarding the fundamental physics of superconductivity, concentrating on the AC losses in superconducting coils and tapes. Overall, the thesis signifies an important contribution to the investigation of High Temperature Superconductors. This thesis will be beneficial to the development of advanced superconducting applications in healthcare as well as more broadly in electrical and energy systems.
Introduction -- Literature Review -- Numerical Modelling and Theoretical Analysis -- Magnet Design for Lorentz Force Electrical Impedance Tomography -- Optimization of the Superconducting Halbach Array -- Lorentz Force Electrical Impedance Tomography System Design.-Investigation of AC Losses on Stabilizer-Free and Copper Stabilizer High Temperature Superconductor Tapes -- Study on Power Dissipation in High Temperature Superconductor Coils -- Investigation of AC Losses in Horizontally Parallel High Temperature Superconductor Tapes -- Conclusion and Future Work.
Keywords: Electrical engineering; Chemistry; Superconductivity; Superconductors; Cancer research; Power electronics; Electrical Engineering; Chemistry/Food Science, general; Strongly Correlated Systems, Superconductivity; Cancer Research; Power Electronics, Electrical Machines and Networks